Impulsive Buying Behavior of Consumers at Bhatbhateni Supermarket in Damak, Jhapa - Poudel, Prakash (New Journey, 2024)
Impulsive buying behavior, characterized by spontaneous and unplanned purchases, presents a significant area of interest in consumer research. This study explores the factors influencing impulsive buying behaviors among consumers in supermarkets located in Damak, Nepal. Drawing upon a quantitative approach, data was collected from 144 respondents using a structured questionnaire. The study investigates the relationships between impulsive buying behaviors and various demographic and situational factors including location, income, and store environment. Results reveal moderate positive correlations between buying behavior and location (r = 0.356), income (r = 0.281), and store environment (r = 0.378), indicating that these factors influence consumer purchasing habits to some extent. Hypothesis testing confirms significant relationships between location, income, store environment, and impulsive buying behavior. The findings underscore the importance of understanding consumer demographics and shopping habits for businesses seeking to influence consumer behavior and design effective marketing strategies. This study contributes to the existing literature by providing insights into the complex interplay of factors shaping impulsive buying behaviors in the context of supermarket shopping in Damak, Nepal.